Exploring the teachers’ practices of corrective feedback in teaching Speaking: A case at an English center - Phan, Ngoc Thach; Nguyen, Hoai An (Tạp chí Khoa học Đại học Đồng Tháp, 2023)
As a teacher, providing corrective feedback is an opportunity to guide students toward success and help them achieve their full potential. By identifying areas where learners need improvement and offering guidance on correcting mistakes, teachers can help their students reach their full potential in English language proficiency. It is essential to deliver feedback in a constructive and supportive manner, focusing on specific areas for improvement rather than criticizing them. The paper explores teachers’ practices using corrective feedback in teaching Speaking at an English center. Twenty teachers participated in the survey to give their general understanding of Corrective feedback. The study gathered data from different sources: interviewing and observing three teachers in the Speaking classrooms. The findings discovered that teachers are aware of the vital of corrective feedback in teaching Speaking. There were judgments between teachers’ beliefs and practices. Recasts and Metalinguistic are two sorts of Corrective Feedback usually provided in this classroom at an English center.